2021
DOI: 10.1186/s13244-021-01008-3
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI radiomics of bone and soft-tissue sarcomas: a systematic review of reproducibility and validation strategies

Abstract: Background Feature reproducibility and model validation are two main challenges of radiomics. This study aims to systematically review radiomic feature reproducibility and predictive model validation strategies in studies dealing with CT and MRI radiomics of bone and soft-tissue sarcomas. The ultimate goal is to promote achieving a consensus on these aspects in radiomic workflows and facilitate clinical transferability. Results Out of 278 identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…Finally, due to the heterogeneity and limited numbers of studies, we only rated the evidence level of radiomics in prediction of NAC response. Further investigation is needed to lay a more robust scientific basis for translating the radiomics approach to a clinical useful tool [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, due to the heterogeneity and limited numbers of studies, we only rated the evidence level of radiomics in prediction of NAC response. Further investigation is needed to lay a more robust scientific basis for translating the radiomics approach to a clinical useful tool [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, despite the promising results, further efforts are needed to make sarcoma radiomics studies reproducible with an acceptable level of evidence. In this context, Gitto et al investigated the reproducibility and validation strategies, and found a huge variation among different studies, thus mining the introduction of TA in the clinical setting [195].…”
Section: Texture Analysis and Prognosis-focus On Other Cancersmentioning
confidence: 99%
“…Sarcomas are solid tumors originating from the mesenchymal tissue and are classified as osteosarcoma and STSs [ 1 ], with more than 50 histological types. The incidence of human osteosarcoma and STS is 1 per 100,000 and (4-5)/100,000 per year, respectively, accounting for approximately 1% of all malignancies [ 2 ]. Despite the fact that STSs can arise anywhere in the body, extremities account for 60–70% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%